Pengaruh Media Kartu Bergambar Terhadap Kemampuan Membaca Pemahaman Siswa Kelas III SDS Muhammadiyah 5 Kota Tangerang - Zuanita Hershifani Uthantry; Een Unaenah, Candra Puspita Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the differences in reading comprehension skills using picture card media among third-grade students of SDS Muhammadiyah 5 Kota Tangerang. The research employed a quantitative approach with a quasi-experimental method, specifically the nonequivalent control group design. The population consisted of all third-grade students at SDS Muhammadiyah 5 Kota Tangerang, totaling 55 students. The research sample comprised two classes: the control class and the experimental class. Data collection techniques included tests, interviews, documentation, and observation. The pre-test and post-test items administered demonstrated strong reliability, with a Cronbach’s Alpha value greater than 0.388. In the t-test hypothesis testing, the post-test data for the control and experimental classes showed that the calculated t-value (t_calculated) was greater than the t-table value (5.226 > 1.673). Based on these results, the alternative hypothesis (H₁) was accepted, and the null hypothesis (H₀) was rejected. Thus, it can be concluded that there is a significant difference in reading comprehension skills when using picture card media among third-grade students of SDS Muhammadiyah 5 Kota Tangerang.